Assessment of the diagnostic value of serum cathepsin S and its correlation with HDL subclasses in patients with non-Hodgkin's lymphoma - Mirjanić-Azarić Bosa; Stanković Siniša; Radić-Savić Zana; Malčić-Zanić Dragana; Ninić Ana; Vuković Marija; Nezić Lana; Skrbić Ranko; Bogavac-Stanojević Nataša (Journal of Medical Biochemistry, 2024)
Background: Recent findings point to the key role of cathepsin S (CTSS) in the survival of malignant cells, as well as the significance of the anti-apoptotic properties of high-density lipoprotein (HDL) that contribute to enhanced cell survival. The purpose of this study is to analyse CTSS as a potential biomarker in lymphoma. Also, in order to better understand the role of CTSS in the origin and development of lymphoma, its association with cystatin C (Cys C), lipids, and inflammatory markers was analysed. Methods: The study included 90 subjects: 11 Hodgkin (HL) and 44 B-cell non-Hodgkin lymphoma (NHL) patients, as well as 35 healthy subjects. CTSS was determined using the Invitrogen ELISA kit (Thermo Fisher Scientific, Inc., Waltham, MA, USA). The non-denaturing 3%-31% polyacrylamide gradient gel electrophoresis method was used to separate plasma HDL particles. Results: The level of CTSS was significantly higher in NHL patients than in control subjects: 12.20 (9.75-14.57) vs 9.97 (8.44-10.99), P<0.001. In NHL patients, there was a positive correlation between CTSS and the proportions of HDL3a, HDL3b, and the sum of the HDL3 subclasses (r=0.506, P<0.001; r=0.411, P=0.006, r=0.335, P=0.026, respectively). In addition, the area under the receiver operating characteristic curve (AUC curve) of CTSS was 0.766 (CI: 0.655-0.856) for NHL patients. There was no significant difference in CTSS values between the control group and patients with HL, nor significant correlations between CTSS and HDL subclasses in the HL group. Conclusions: CTSS is significantly elevated in patients with NHL and has the potential to be a new diagnostic bio - marker for the detection of NHL. Also, this study was the first to unveil the association between serum CTSS levels and the proportions of anti-apoptotic HDL3a and HDL3b subclasses in NHL patients.